2021
DOI: 10.1016/j.heliyon.2021.e06156
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a domestic refrigerator in varying ambient temperatures, concentrations of TiO2 nanolubricants and R600a refrigerant charges

Abstract: This study investigates the effect of varying test conditions including ambient temperature (19, 22, and 25 C), mass charges of R600a refrigerant (40, 50, 60, and 70 g), and concentrations of TiO 2 nanolubricant (0, 0.2 and 0.4 g/L) on the performance of a slightly modified 100g R134a domestic refrigeration system. The investigated parameters include evaporator air temperature, energy consumption, coefficient of performance, and second law efficiency of the system. The results showed that the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This phenomenon is attributed to the impact of increasing the refrigerant mass flow rate for each initial refrigerant charge, which affects the compressor power input. This trend aligns with the findings reported by Adelekan et al [ 11 , 68 ]. The experimental results demonstrated that the use of nanolubricant decreased compressor work by 4.91%–17.23%.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This phenomenon is attributed to the impact of increasing the refrigerant mass flow rate for each initial refrigerant charge, which affects the compressor power input. This trend aligns with the findings reported by Adelekan et al [ 11 , 68 ]. The experimental results demonstrated that the use of nanolubricant decreased compressor work by 4.91%–17.23%.…”
Section: Resultssupporting
confidence: 93%
“…Pure POE lubricant is introduced into the RAC system at the commencement of each assessment for the next concentration. This is done to prevent any contamination from the previous nanolubricant to the succeeding one [ 11 ]. This process is repeated three times for the FAl2O3-POE nanolubricant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there is a reduction in power consumption from 3.09 to 25.13% with R600a refrigerant when compared to R134a refrigerant. The observed low power consumption of the system with hydrocarbon refrigerants resulted from low viscosity and pressure drop [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adelekan et.al. [19][20][21] enhanced the COP by 2.99 to 10.94 percent by using titanium oxide nanoparticles at different concentrations and varied ambient temperatures at 19, 22 and 25 0 C.and also resulted with highest COP of 4.99 with 0.1g/L of titanium oxide and 40g of R600a and enhanced cooling effect of 290.33 kJ/kg.performed experiments with varied concentrations of graphene nanolubricants and varied mass charges of R600a refrigerant. The maximum COP of 0.76 and less power utilized by the compressor by 65W was obtained.…”
Section: Introductionmentioning
confidence: 99%